Staged data delivery protocol: A blockchain‐based two‐stage protocol for non‐repudiation data delivery. (1st March 2021) - Wang, Liang; Liu, Jiayan; Liu, Wenyuan
Abstract: For many years, non‐repudiation in data delivery has not been satisfactorily achieved due to the difficulty of supervising delivery behavior. Existing fair protocols are still not entirely free of third parties who are usually not as trustworthy as expected. Moreover, most of them are built on complex encryption schemes, resulting in inefficiencies when handling large chunks of data and non‐exchanged data sharing. To be able to deliver data without third parties and repudiation, we propose the staged data delivery protocol (SDDP) that integrates fair data delivery into Blockchain consensus processes. SDDP confirms transactions of data delivery in a cascading manner where nodes sign on each transaction one after another. It consists of two stages, in which neither party will have a considerable advantage over the other. In this way, SDDP enables non‐repudiation of directly delivering large chunks of data through an understandable communication strategy; and the Blockchain network replaces third parties to preserve an immutable history of data delivery activities. The results of extensive evaluations show that SDDP is admissible for dealing with fair data delivery on the basis of its good qualities and performance.